Building a Virtual Research Environment for the Humanities JISC Final Report - Kirkham, R (2007)
The survey has highlighted the need for a simple to use, easy to access interface which underpins all stages of the research life-cycle, highlighting the need for tools and services to support: • Research administration; • Resource discovery; • Data creation, use and analysis; • Collaboration and communication; • Publication, curation and preservation Research administration: Interviewees want seamless access to information about events, including conferences, lectures and seminars; research and researcher interests of individuals within the institution and beyond; and information regarding grants and funding opportunities, all of the above accessible in one, easy to navigate place. Resource discovery: Interviewees wish to make the process of finding resources and research material more efficient by linking datasets and databases so that they can be cross searched with a single search term and the results returned to personal area for future reference. Data creation, use and analysis: Interviewees want a secure area in which they can store material such as saved searches, images and texts; create notes and annotations and use tools to enhance, manipulate and compare items. Collaboration and communication: Interviewees want tools to enable them to work collaboratively on documents, to share material with collaborators and to view material simultaneously with colleagues wherever they might be based. At the same time interviewees want to communicate either through video conferencing or real time chat facilities and to enable a collaborator to point/highlight and annotate items throughout the discussion. Publication, curation and preservation: Interviewees wish to store, publish and archive their work both on personal web pages for open access or in a more secure area for academic material. Interviewees want to be sure that their work and the work of those around them is preserved and made available both within Oxford and externally to promote the division and its work.